Penerapan Model PBL Berbasis Kearifan Lokal Adaptasi Masyarakat Kupang Terhadap Iklim Kering Untuk Meningkatkan Keterampilan Berpikir Kritis Dan Keaktifan Belajar Siswa SD - Muhsam, Julhidayat; Nurlaila; Hasyda, Suryadin (Program Studi Pendidikan Guru Sekolah Dasar-Universitas Muhammadiyah Kupang, 2026)
This study aims to improve critical thinking skills and learning activity of elementary school students through the application of the Problem Based Learning (PBL) model based on local wisdom of community adaptation to the dry climate of Kupang. This study uses the Classroom Action Research method with the Kemmis and McTaggart model which is implemented in two cycles, each including the planning stage, action implementation, observation, and reflection. The research subjects were 27 fourth-grade students of Sikumana 1 Elementary School. The research instruments included a critical thinking skills test and an observation sheet of student learning activity. Data were analyzed using quantitative descriptive analysis by comparing the results between cycles. The results showed that the application of the local wisdom-based PBL model was able to significantly improve critical thinking skills and student learning activity from cycle I to cycle II. The integration of local wisdom of Kupang community adaptation to the dry climate makes learning more contextual, meaningful, and encourages active student involvement in the learning process.